2011
DOI: 10.1016/j.biomaterials.2011.07.079
|View full text |Cite
|
Sign up to set email alerts
|

Engineering fibrin-binding TGF-β1 for sustained signaling and contractile function of MSC based vascular constructs

Abstract: We present a strategy to conjugate TGF-β1 into fibrin hydrogels to mimic the in vivo presentation of the growth factor in a 3D context. To this end, we engineered fusion proteins between TGF-β1 and a bi-functional peptide composed of a Factor XIII domain and a plasmin cleavage site. In another version the protease cleavage site was omitted to examine whether the growth factor that could not be released from the scaffold by cells had different effects on tissue constructs. The optimal insertion site which yield… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 64 publications
1
45
0
Order By: Relevance
“…Previous work in our laboratory has shown that fibrin immobilized TGF-b1-promoted MSC differentiation to SMCs uniformly throughout fibrin rings, eliminating growth factor diffusion limitations. 33,42 VEGF has been used to promote angiogenesis in many previous studies, however, neovessels formed only in the presence of VEGF have been shown to be unstable and degrade rapidly in vitro, and at a slower extent in vivo. This is likely due to the lack of pericytes and SMCs, which typically enwrap neovessels within the body.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous work in our laboratory has shown that fibrin immobilized TGF-b1-promoted MSC differentiation to SMCs uniformly throughout fibrin rings, eliminating growth factor diffusion limitations. 33,42 VEGF has been used to promote angiogenesis in many previous studies, however, neovessels formed only in the presence of VEGF have been shown to be unstable and degrade rapidly in vitro, and at a slower extent in vivo. This is likely due to the lack of pericytes and SMCs, which typically enwrap neovessels within the body.…”
Section: Discussionmentioning
confidence: 99%
“…Fibrin has been extensively studied as a scaffold and a number of studies have shown that fibrin is a growth factor carrier for tissue regeneration. 33,42 In addition, fibrin has also been used to deliver stem cells for bone tissue engineering. 43,44 Ideally, incorporation of a vascularized network into engineered bone substitutes to mimic the structure of natural bone tissue is necessary to promote rapid bone regeneration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8,25,[27][28][29] In the current study, the same protocol was used to prepare TEV constructs by polymerizing fibrin hydrogels around the silastic tubing on the 24-PP, which measures 4.75 mm in diameter. 10 6 cells of each cell isolation were suspended in 800 mL of fibrinogen (Enzyme Research Laboratories) and mixed with 200 mL of thrombin (Sigma) with final concentrations of 2.5 mg and 2.5 U, respectively.…”
Section: Preparation Of Tissue-engineered Vessels On the 24-ppmentioning
confidence: 99%
“…77 Recent studies showed that biomaterials can be decorated with various biomolecules to provide appropriate growth or differentiation signals as necessary. [78][79][80][81][82][83] It might be interesting to examine whether this approach could be applied in the context of HFs to overcome the current limitations and facilitate studies of human HF biology.…”
Section: Human Hfsmentioning
confidence: 99%